Exploration of anthelmintic activity of Cassia spp. extracts on gastrointestinal nematodes of sheep - Wahyuni, Sri; Sunarso, Sunarso; Prasetiyono, Bambang Waluyo Hadi Eko; Satrija, Fadjar (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aimed to explore the phytochemical constituents and anthelmintic activities of four Cassia spp. leaves against Haemonchus contortus. Materials and Methods: The extracts were prepared from four species of Cassia spp. (C. siamea, C. fistula, C. surattensis, and C. spectabilis). Phytochemical screening of the extract was done based on the Harborne method. Evaluation of the anthelmintic activities against H. contortus was done in vitro using infective larvae (L3) migration inhibition assay (LMIA). Measurement of larvae migrating was conducted through a nylon filter with a pore size of 20 μm. The doses of Cassia spp. extract implemented were 25, 50, 100, and 200 mg/ml. Results: Tannins, alkaloids, phenol hydroquinone, flavonoids, steroids, triterpenoids, and saponins were present in all the extracts, whereas alkaloids were absent in C. fistula. No triterpenoids were found in C. surattensis and C. spectabilis. Movement of H. contortus larvae was significantly inhibited after exposure to Cassia extracts at various dosage levels (p < 0.05). The test results using LMIA on L3 H. contortus showed the lowest inhibition in the negative control. Among the species of Cassia, the C. surattensis (at 200 mg/ml) showed the highest (p < 0.05) inhibition level on the larvae. The latter result corresponded to the effect of albendazole. Conclusion: Compared to other Cassia spp., C. surattensis exhibited the highest inhibition against L3 H. contortus. However, the inhibition effect of C. surattensis was still lower as compared to albendazole. J. Adv. Vet. Anim. Res., 6(2): 236-240, June 2019